Dynamic links between financial development and CO2 emissions in Nigeria: evidence from ARDL bound test framework - Ali, Hamisu Sadi; Law, Siong Hook; Yusop, Zulkornain; Lee, Chin (Faculty of Economics and Administration, University of Malaya, 2015)
Using ARDL bound test approach for the period of 1971-2010 the present article examined the links between financial development, energy consumption, trade openness, economic growth and CO2 emissions in Nigeria. The result reveals that variables were cointegrated as null hypothesis was rejected at 5% level of significance. Furthermore based on short run dynamics, financial development, economic growth and energy consumption have positive significant impact on CO2 emissions, while trade openness have negative insignificant impact on CO2 emissions. In the long-run however, the finding proved that financial development, economic growth and energy consumption have positive and significant influence on CO2 emissions, while trade openness has negative significant impact on CO2 emissions in Nigeria. The policy implication is that Nigerian public authority should focus more on initiating environmentally friendly policies that can reduce carbon emissions and explore other alternative sources of energy considering its movement with the financial sector performance. Proper trade liberalization policies should be put in place considering its roles in reducing carbon emission that will improve environmental quality in the country.